SALAFI MUDA DAN KEPEMILIKAN BISNIS: KEWENANGAN PEREMPUAN MUDA SALAFI MENGELOLA BISNIS ONLINE - Dwi Nugroho; Angga Febrian; Dharma Setyawan (Balai Penelitian dan Pengembangan Agama Jakarta, 2024)
Salafi women are regarded as a more tight and exclusive community than men. This reality highlights Salafi Sharia provisions, which mandate women to stay at home. Nonetheless, young Salafi women are beginning to engage in productive activities by tapping business opportunities of digital economy. This study is based on a massive phenomenon regarding the involvement of young Salafi women in digital entrepreneurial activities. Using a case study of Salafi women in Lampung with purposive sampling technique, it analyzes data from in-depth interviews with 13 young Salafi women who run online enterprises and 2 men (ustadz and teacher) served as the main sources for this explorative qualitative research. This study demonstrates that apart from accepting technological advances, Salafi women also actualize themselves in digital economic activities. They can run successful online businesses and have a positive impact on their financial emancipation. Their internet commercial activities strictly adhere to Islamic law and not limited to products associated with Salafi life. Their activities do not deviate from Islamic norms and instead reflect the Salafis’ productive and reformist characteristics. Challenging conventional wisdom on Salafi women, this study finds that within their submission to Salafi teachings and piety, they claim their active agency and contributions to family economy.